The Effect of Drying Air Velocity and Grain Mass on the Drying Rate of Inpari 42 Grain in a Fluidized Bed Dryer. - Ibrahim, A. Muh. Farhan Qibran; Salengke, Salengke; Salim, Iqbal; Hardinasinta, Gemala (Program Studi Teknik Pertanian Universitas Hasanuddin, 2023)
Statistical data shows that rice production increases every period along with the increase in demand. Harvested paddy must be dried immediately to avoid damage due to microbial attack that can live in high moisture content. Therefore, the main objective of drying is to reduce the moisture content from the harvest moisture content (23-27%) to a safe moisture content for storage (14%). Currently, there are several dryers made as a solution in post-harvest handling of grains such as green beans, soybeans, grain and so on. One example of this dryer is the Fluidized Bed Dryer. This tool is a mechanical dryer that can be used in drying grain. The advantage of this tool is that the temperature can be controlled and can produce quality and uniform drying results. The purpose of this study was to determine the drying characteristics of Inpari 42 grain using a fluidized bed dryer. This research method uses speed variations of 1.5 m/s, 2.0 m/s, and 2.5 m/s with sample masses of 200 g, 250 g and 300 g, using a temperature of 55 ℃. The research parameters include moisture content, drying rate, damaged grain. The drying process shows that the change in sample mass is influenced by the air velocity used. Along with the increase in moisture content, the drying rate will affect the rate of drying obtained in this study the drying rate pattern is decreasing. It can be concluded that air velocity affects the drying rate and air velocity affects the cracked grain.